Pediatrician′s perspectives on dental trauma management: A cross-sectional survey - H P Chanchala; Raghavendra Shanbhog; M D Ravi; Vidhya Raju (Journal of Indian Association of Public Health Dentistry, 2016)
Introduction: Pediatricians play a pivotal role in the provision of primary care following dental trauma, especially for population with limited access to dental care. The criticality of time and knowledge is very important in the success of dental trauma management. Objective: The objective of this study was to evaluate the knowledge and experience of pediatricians in the primary management of dental trauma. Materials and Methods: A questionnaire-based cross-sectional survey was conducted among 261 pediatricians from various regions of India who attended the National Pediatric Conference, Mysore 2015. The survey addressed demographic- and knowledge-related data concerned to dental trauma, experience in treating and witnessing dental trauma, diagnosis, preliminary management, and attitude of the pediatricians toward the same. The collected data were analyzed using the SPSS version 17. Results: Among 261 respondents analyzed, 65.5% of them had encountered dental trauma in their practice. Avulsed tooth can be saved as opined by 67.8% of pediatricians. A higher percentage of the pediatricians, 94.3% knew the significance of time lapse. Saline was preferred medium of transport by 90.8%, followed by ice-cold water (78.2%). A fair awareness of the emergency treatment protocol of the avulsed teeth was observed among 59.8% of the pediatricians. Conclusion: Among pediatricians, the knowledge regarding handling of avulsed tooth, medium of transportation, and significance of time lapse between avulsion and reimplantation were found to be at a good level. The knowledge regarding the type of tooth to be reimplanted, method of cleaning the tooth was lacking.